1977
DOI: 10.1203/00006450-197707000-00013
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Antenatal Corticosteroids on Hypoglycemia in Newborn Rats with Intrauterine Growth Retardation

Abstract: Dysmaturity hypoglycemia fctus intrauterine growth retardation glucocorticoid livcr glycogcn

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

1977
1977
1993
1993

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…In accord with other investigations, in trauterine undernutrition secondary to uter ine vessel ligation resulted in neonatal growth retardation and significantly lowered blood glucose levels at 4 h of life [9,13,20]. Our data also demonstrate that although surgical IUGR marginally enhances levels of neonatal renal PEPCK at 4 h, this renal gluconeogenic activity is insufficient to maintain glycemia at levels found in controls.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In accord with other investigations, in trauterine undernutrition secondary to uter ine vessel ligation resulted in neonatal growth retardation and significantly lowered blood glucose levels at 4 h of life [9,13,20]. Our data also demonstrate that although surgical IUGR marginally enhances levels of neonatal renal PEPCK at 4 h, this renal gluconeogenic activity is insufficient to maintain glycemia at levels found in controls.…”
Section: Discussionsupporting
confidence: 76%
“…None theless, the induction of PEPCK by glucocor ticoids in the developing kidney may play a role in utero, since there are significant in creases in renal PEPCK at birth in the dexa methasone IUGR group. Manniello et al [13,14] demonstrated that prenatal treat ment of growth-retarded rat neonates with glucocorticoids raised blood glucose to levels approximating those of normal weight neo nates at 2-6 h of life and elevated gluconeo genic amino acids levels and liver glycogen content. No significant effect of treatment, however, was noted in the glucose pattern of controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The available literature allows one to agree with the opinion that cor ticosteroids given to the mother may protect her infant against postnatal hypoglycemia (at least, in the case of rats [4]). Yet, from other studies opposite suggestions may be drawn out.…”
mentioning
confidence: 78%
“…We have previously shown that 91 % of dysmature rat pups develop hypoglycemia 2-4 hr after birth and that prenatal glucocorticoid treatment significantly reduces this tendency (2). Our subsequent invcstigations have included an examination of the possible relationship between the protective effect of steroid hormones and the availability or utilization of gluconeogenic substrates.…”
mentioning
confidence: 99%